FUNGSI DAN KEDUDUKAN ADVOKAT DALAM PROSES PENEGAKAN HUKUM DI INDONESIA - Raden Muzayyin Arifin (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2015)
Advocate in Law No. 18 Year 2003 concerning Advocates Law Enforcement domiciled is on par with other law enforcement, such as police, prosecutor and judge. As law enforcement, advocates in their duties is framed by a set of code of conduct in order to advocate professional in their duties. Advocates in carrying out its duties and functions continue to struggle in the struggle to reach the truth, justice, liberty and equality for its clients in order not terdhalimi in the legal process path. In international agreements, as contained in the Basic Principles on the Role of Lawyers (Adopted by the Eighth Crime Congress, 1990), can be seen in the international community recognition of the importance kedudukaan pensihat law. Within this international document set principles that prove how important the position of legal counsel in the criminal justice system. The success of law enforcement in fact influenced also by the role and responsibilities of the group of legal counsel. Justice is quick, simple and honest is not solely addressed to the four components of law enforcement that have been prevalent recognized, but also to the group addressed legal counsel as the fifth component.